Study on the Interference Law of AC Transmission Lines on the Cathodic Protection Potential of Long-Distance Transmission Pipelines - Boyang Zhang; Lin Li; Yansong Zhang; Jielin Wang (Magnetochemistry, 2023)
Through inductive coupling, AC transmission lines can generate large amounts of voltage to buried oil and gas pipelines in areas with common corridors, posing a threat to the cathodic protection effect of pipelines. Therefore, this paper investigates the effect of AC transmission lines on the cathodic protection of long-distance pipelines through inductive coupling. COMSOL Multiphysics finite element simulation software is used to calculate the distribution of cathodic protection potential of long-distance pipelines under different voltage levels, parallel spacing, conductor-to-ground height, conductor arrangement and pipeline burial depth for normal operation of AC transmission lines. Comparison and analysis of the AC transmission line on the pipeline cathodic protection potential interference law is conducted. The results show that: 1. AC transmission lines cause serious electromagnetic interference with the pipeline cathodic protection system, which will cause the pipeline cathodic protection potential to shift out of the effective protection area. 2. The maximum value of the induced voltage of the pipeline will appear at the two ends of the pipeline, and the induced voltage of the pipeline in the middle position is 0. 3. The shift of the pipeline cathodic protection potential increases with the increase of voltage level and decreases with the increase of parallel spacing, conductor height and burial depth. The pipeline cathodic protection potential shift is highest when the wires are arranged horizontally and lowest when they are arranged in an umbrella shape.